IODINE-131 RESISTANCE IN A CASE OF TOXIC ADENOMA REQUIRING MULTIPLE COURSES OF RAI-131 - Raman, Muhamad Fazrin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyperthyroidism is a state of hyperactive thyroid gland secreting excessive thyroid hormone causing a constellation of symptoms to multiple organs and systems. Hyperthyroidism can be caused by an autoimmune condition (Graves’ disease), inflammation of the thyroid (thyroiditis), or due to functioning thyroid nodules (hot nodule or toxic multinodular goitre). We report a case of toxic adenoma, who received Iodine-131 four times with a cumulative dose of 69 mCi; however, persistent hyperthyroidism required additional treatment with ATD. Subsequently, she underwent left hemithyroidectomy. CASE A 29-year-old female was referred to the nuclear department for radioactive iodine-131 (RAI-131) therapy. She received her first RAI-131 with 15 mCi in September 2020. Due to persistent hyperthyroidism, she received another RAI131 with 15 mCi in April 2021. Her third RAI-131 with 21 mCi done in January 2022 and fourth RAI-131 with 18 mCi was done in June 2022 due to persistent hyperthyroidism requiring ATD. She had Tc-99 m pertechnetate thyroid uptake scan done with scan findings suggestive of toxic multinodular goitre in left thyroid lobe. She was planned for another RAI-131, however she refused. Left hemithyroidectomy done in September 2023 with HPE reported as nodular hyperplasia with dominant nodule and cystic degeneration. She developed transient hypothyroidism after surgery requiring levothyroxine and subsequently euthyroidism without any medication. CONCLUSION RAI-131 is relatively safe and easy to administer making it the treatment of choice for many causes of hyperthyroidism. Around 10% of patients would require subsequent dose of RAI-131. Failure of RAI-131 for treatment of hyperthyroid is rare, mainly due to inadequate preparation. Some patients have delayed response to RAI-131, up to years after iodine treatment.